2018
DOI: 10.1016/j.cobeha.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious psychological treatments for physiological survival circuits

Abstract: The idea of targeting unconscious or implicit processes in psychological treatments is not new, but until recently it has not been easy to manipulate these processes without also engaging consciousness. Here we review how this is possible, using various modern cognitive neuroscience methods including a technique known as Decoded Neural-Reinforcement. We discuss the general advantages of this approach, such as how it can facilitate double-blind placebo-controlled studies, and minimize premature patient dropouts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 83 publications
(81 reference statements)
1
15
0
Order By: Relevance
“…A higher-order perspective is in line with previous results 12, [26][27][28][29] and ours, but models of emotions are still being debated 30 . For instance, one may argue against this hierarchical or higher-order view based on experimental demonstrations that the electrical stimulation of the amygdala itself can trigger a subjective experience of fear and anxiety 31 .…”
Section: Figure 3 Whole-brain Decoders Of Subjective Fear and Skin Csupporting
confidence: 91%
“…A higher-order perspective is in line with previous results 12, [26][27][28][29] and ours, but models of emotions are still being debated 30 . For instance, one may argue against this hierarchical or higher-order view based on experimental demonstrations that the electrical stimulation of the amygdala itself can trigger a subjective experience of fear and anxiety 31 .…”
Section: Figure 3 Whole-brain Decoders Of Subjective Fear and Skin Csupporting
confidence: 91%
“…As a result, some authors have called for caution in the direct association of implicit brain processes with subjective emotional states. This position is still controversial and is at the center of much recent debates and discussion (Fanselow & Pennington, 2017LeDoux & Brown, 2017;LeDoux & Pine, 2016;Pine & LeDoux, 2017;Taschereau-Dumouchel, Liu, et al, 2018) .…”
Section: Discussionmentioning
confidence: 99%
“…Another unanswered question regarding the potential therapeutic applications of neural reinforcement pertains to its capacity to change the subjective experience of fear. While physiological reactivity is undoubtedly an important mechanism of anxiety disorders (Etkin & Wager, 2007) , there is also evidence suggesting that physiological reactivity might dissociate from the subjective fear reports (LeDoux & Brown, 2017;LeDoux & Pine, 2016;Taschereau-Dumouchel, Liu, et al, 2018) .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, modulating neural activity in the medial PFC during or immediately after extinction has been shown to enhance extinction retention [44,45] and improve exposure outcomes among individuals with PTSD [46]. Another promising method of neuromodulation is a technique called decoded neural reinforcement, which involves rewarding unconscious neural representations of feared stimuli as a way of counter-conditioning fear [47]. Early studies have shown such an approach can decrease fear responses to laboratory conditioned fears [48] as well as pre-existing fears of specific animals (e.g., snakes, cockroaches) [49].…”
Section: Successes Of the Extinction Modelmentioning
confidence: 99%